تقنية التجميع المحاسبي بين المرجعية المحاسبية الجزائرية والمرجعية المحاسبية الدولية: دراسة تحليلية مقارنة - بوجاجة إبراهيم; بولحية عفاف (جامعة الوادي University Of Eloued, 2024)
This research paper seeks to identify the concepts related to the issue of accounting Consolidation in addition to highlighting the differences between commercial law and (SCF), and between (SCF) and international accounting standards, and in order to achieve this purpose, the research provides a comparative analytical study between the Algerian accounting framework and the international framework. In the end, the research paper concluded with a set of results, the most important of which is the existence of some differences between SCF and commercial law, such as links between companies, so that we found that commercial law was limited to financial links, while SCF added operational links, as well as we concluded that although SCF is compatible with the international frameworkin terms and concepts related to aggregation, unlike commercial law, both lack a clear legal framework that regulates the process of compiling accounts .
Consolidation Accounting Techniques between the Algerian accounting framework and the international accounting framework: a comparative analytical study
Keywords: القوائم المالية المجمعة; طرق التجميع; النظام المحاسبي المالي; معايير المحاسبة الدولية; الرقابة; Consolidated financial statements; Consolidation; methods; Financial Accounting System; International Accounting Standards; Control